HGG-45. COMPREHENSIVE MOLECULAR CHARACTERIZATION OF PEDIATRIC TREATMENT-INDUCED HIGH-GRADE GLIOMA: GERMLINE DNA REPAIR DEFECTS AS A POTENTIAL ETIOLOGY. Issue 2 (22nd June 2018) - DeSisto, John; Lucas, John; Donson, Andrew; Sanford, Bridget; Wu, Gang; Armstrong, Gregory; Arnold, Michael; Bhatia, Smita; Flannery, Patrick; Lemma, Rakeb; Hardie, Lakotah; Hoffman, Lindsey; et al.
Abstract: BACKGROUND: Pediatric treatment-induced high-grade glioma (TIHGG) is an incurable late complication of cranial radiation therapy or combined radiation/chemotherapy. Previously, we showed TIHGG gene expression differs from spontaneous pediatric HGG and defined two TIHGG groups (A & B) by transcriptomic profiling. We now report copy-number analysis, whole genome sequencing (WGS), and methylation profiling for an expanded TIHGG cohort. METHODS: Illumina Infinium 450/850K methylation analysis was performed on 34 TIHGG samples from a multi-institutional/Childhood Cancer Survivors Study Group cohort. WGS was performed on tumor and matched germline DNA from 15 TIHGGs. RESULTS: On methylation profiling, 19/27 TIGs, including all expression group A and B cases (6 each), clustered into a subclass of IDH-wt midline GBM. Recurrent copy number alterations included 1p loss (13/34), 1q gain (13/34), ch13 loss (13/34), PDGFRA gain/amplification (17/34), and CDKN2A loss (14/34). WGS identified a mean germline mutation load of 1.50 mut/Mb. Mean somatic mutation load, excluding one hypermutator sample, was 0.12 and 1.08 mut/Mb for TIHGG expression groups A and B, respectively (p<0.002). All TIHGG group B cases had pathogenic germline alterations in BARD1 or BRCA1, which repair DNA damage from ionizing radiation. TIHGG expression group A samples lacked pathogenic DNA repair mutations, except the hypermutator sample, which had distinct germline DNA repair defects including BRCA2 and ATR. CONCLUSIONS: TIHGGs are enriched for distinctive chromosomal aberrations and cluster into a defined epigenetic subgroup. A subset of TIHGGs have a high somatic mutational load, likely from germline defects in homologous recombination, which could predict TIHGG risk before treatment.